Everyone dies a Kevin Kerney novel - McGarrity, Michael (New York : Dutton, 2003)
Eagerly awaiting the birth of his first child when a prominent homosexual lawyer is murdered, Santa Fe police chief Kevin Kerney directs his staff along elusive leads that result in two additional deaths and the discovery of a chilling series of killings.
82381
Keywords: Kerney, Kevin (Fictitious character) -- Fiction; Police -- New Mexico -- Santa Fe -- Fiction; Gay men -- Crimes against -- Fiction; Santa Fe (N.M.) -- Fiction; Serial murders -- Fiction; Police chiefs -- Fiction; Mystery fiction